The Effects of Environmental Enrichment and Impoverishment on an Animal Model of Depression and Anxiety: Brain, Behaviour and Immune Function - Mileva, Guergana (Université d'Ottawa / University of Ottawa, 2016)
While women are diagnosed with depression at twice the rate of men, pre-clinical research on this topic has relied heavily on the responses of male animals. This thesis examined the behavioural and physiological effects of environmental manipulation in the female Wistar-Kyoto rat, a putative animal model of depression. At postnatal day 52, baseline behavioural measures were collected in 36 Wistar and 36 Wistar-Kyoto female rats using the following tests: the elevated plus maze to assess anxiety, the forced swim test for depression-like behaviour, and sucrose preference test to assess hedonic status. At postnatal day 62, the rats were randomly assigned to one of three environments for 30 days: 1) standard housing - 3 rats in one large cage 2) isolated housing - 1 rat per small cage, or 3) environmental enrichment - 6 animals in a multistory cage filled with novel objects and a running wheel. Following 30 days in their housing condition, the same behavioural measures were again collected. Large differences between strains were found with the Wistar-Kyoto females showing significantly less mobility and activity in both the forced swim test and elevated plus maze. Sucrose preference was significantly higher after enrichment in both strains. Post-environment immune cytokine and corticosterone levels were also assessed in these animals at baseline and after the forced swim test. No difference in corticosterone between strains was found at baseline. However, Wistar-Kyoto females had significantly higher corticosterone levels than their Wistar counterparts after the forced swim test. In contrast, Wistar-Kyoto females showed significantly lower serum levels of the pro-inflammatory cytokine IL-1β than Wistar females. In the hippocampus, astroglial staining intensity was significantly increased in the CA1 of Wistar females after environmental enrichment. Glucocorticoid receptor staining in the CA3 was also increased after environmental enrichment in both the Wistar-Kyoto and Wistar animals. Finally there was a trend towards higher levels of glucocorticoid receptors in the amygdala in Wistar-Kyoto animals who experienced environmental enrichment. Taken together, this thesis provides evidence for the effect of environment, specifically enrichment, on behaviour and physiological systems. These results suggest that incorporating social and physical enrichment as part of clinical intervention may benefit individuals with depression.
Keywords: Depression; WKY; Anxiety; Animal Models; Behaviour; Biomarkers; Environment